Corruption, environmental regulation and market entry. (30th August 2016) - Biswas, Amit K.; Thum, Marcel
Abstract: The authors develop a simple analytical framework to study the welfare-maximizing environmental standards when market entry is endogenous and firms can circumvent regulation by bribing corrupt officials. Corruption changes the tradeoff in environmental policy. Corruption leads more polluting firms to enter into the market, which requires tighter environmental regulation. However, corruption also makes trading in some environmental protection for a marginally higher market entry optimal for the government.